2007 IEEE International Symposium on Industrial Electronics 2007
DOI: 10.1109/isie.2007.4374780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Classic and Innovative Sideband-Based Broken Bar Indicators by Using an Experimental Cage and a Transformed (n, m) Complex Model

Abstract: In this work the results of a measuring and simulation campaign performed on an experimental induction motor with artificial broken bars are presented, aiming to extract spectral current components useful for fault detection. With nonsinusoidal feeding a lot of frequencies other than (1-2s)f (lowersideband, LSB) and (1+2s)f (upper-sideband, USB) arise, in proximity of low-order current harmonics, that can be good fault indicators. Current signature analysis-based techniques (CSABT) can take advantage by these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Appendix B. The complete model is reported in [7]. All the circulant matrices turn out in a diagonalized shape in this way, and the sequence circuits are easily decoupled.…”
Section: A Phase Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Appendix B. The complete model is reported in [7]. All the circulant matrices turn out in a diagonalized shape in this way, and the sequence circuits are easily decoupled.…”
Section: A Phase Modelmentioning
confidence: 99%
“…The transformed stator-rotor mutual inductance matrices are as follows:L '-F* L F -b d d' IL (q) )SR -n SR m -an -lag I SR J sequence mutual inductances L,sR (q) , LRS (q) are complex functions of the rotor rotation angle 8:L ( q ) -L ( q ) *-;-A ( q ) j qB 511 -ILl' -'I nm ,1 e . (B24)Since the matrices LSR' and LRS' =(LsR') ' * are usually non-square matrices, their shape is band-diagonal[7] as shown in (B25)for LRS' in case of four-pole machines (n=12).Figs. 12, 13show the real and transformed mutual inductances, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The accurate prediction of rotor bar current in squirrel‐cage induction machines (IMs) is crucial both in terms of electromagnetic performance including the parasitic effects and control of IM drives. In general, it has been assumed that the bar currents are sinusoidal under the balanced three‐phase sinusoidal source and healthy operation conditions [1–3]. Nevertheless, it has been revealed that the bar currents can be non‐sinusoidal under a very low slip rate or excessively high electrical loading operations [4] or in the IMs whose air‐gap length is remarkably short [5].…”
Section: Introductionmentioning
confidence: 99%